A novel human gastric primary cell culture system for modelling Helicobacter pylori infection in vitro. Issue 2 (24th December 2014) - Schlaermann, Philipp; Toelle, Benjamin; Berger, Hilmar; Schmidt, Sven C; Glanemann, Matthias; Ordemann, Jürgen; Bartfeld, Sina; Mollenkopf, Hans J; Meyer, Thomas F
Abstract : Background and aims: Helicobacter pylori is the causative agent of gastric diseases and the main risk factor in the development of gastric adenocarcinoma. In vitro studies with this bacterial pathogen largely rely on the use of transformed cell lines as infection model. However, this approach is intrinsically artificial and especially inappropriate when it comes to investigating the mechanisms of cancerogenesis. Moreover, common cell lines are often defective in crucial signalling pathways relevant to infection and cancer. A long-lived primary cell system would be preferable in order to better approximate the human in vivo situation. Methods: Gastric glands were isolated from healthy human stomach tissue and grown in Matrigel containing media supplemented with various growth factors, developmental regulators and apoptosis inhibitors to generate long-lasting normal epithelial cell cultures. Results: Culture conditions were developed which support the formation and quasi-indefinite growth of three dimensional (3D) spheroids derived from various sites of the human stomach. Spheroids could be differentiated to gastric organoids after withdrawal of Wnt3A and R-spondin1 from the medium. The 3D cultures exhibit typical morphological features of human stomach tissue. Transfer of sheared spheroids into 2D culture led to the formation of dense planar cultures of polarised epithelial cells serving as a suitable in vitro model of H. pylori infection. Conclusions: A robust and quasi-immortal 3D organoid model has been established, which is considered instrumental for future research aimed to understand the underlying mechanisms of infection, mucosal immunity and cancer of the human stomach.